Analisis Ekonomi Penerapan Konservasi Energi Listrik Penerangan Jalan Umum Jalan Jendral Sudirman Kota Pekanbaru - Rian Adli; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One of the efforts that can be done from the depletion of the electric energy sources supply was to reduce the consumption of electric energy. It can be applied to the streetlights without reduced the use of its value. Jendral Sudirman Street Pekanbaru is one of the arterial roads that used conventional lamp SON-T 250 Watt. The existing streetlights condition at Jendral Sudirman street was not standardize at all points that have been set because of it’s not appropriate specification and placement of the pole. The streetlights conservation at Jendral Sudirman street to the 150 Watt LED energy saving lamp be required investment cost of Rp 1,289,666,668, with the electrical energy savings of 15 264 kWh per month and electrical cost savings per month up to Rp 23,265,999.36. The economic analysis which is obtained from the streetlights conservation activities at Jendral Sudirman in the form of NPV (Net Present Value) as much Rp 957,717,056.10, Gross B / C (Gross Benefit Cost Ratio) 1,742, and the payback period of benefits obtained (Payback Period) for 5.727 years.Keywords : Conservation, LED, economic analysis, NPV, Gross B / C, Payback Periode